การพัฒนารูปแบบการดูแลผู้ป่วยเบาหวานโดยการประยุกต์แนวคิดรูปแบบการดูแลโรคเรื้อรังเชิงบูรณาการ จังหวัดพังงา: Development of a Diabetes Care Model by Applying the Integrated Chronic Care Model in Phang Nga Province - จุลแก้ว, ทินกร (วารสารวิชาการกรมสนับสนุนบริการสุขภาพ, 2025)
การวิจัยและพัฒนาครั้งนี้ มีวัตถุประสงค์เพื่อ (1) ศึกษาปัจจัยที่ส่งผลต่อพฤติกรรมการดูแลตนเองในการควบคุมระดับน้ำตาลในเลือดของผู้ป่วยเบาหวาน (2) พัฒนารูปแบบการดูแลผู้ป่วยเบาหวานโดยการประยุกต์แนวคิดรูปแบบการดูแลโรคเรื้อรังเชิงบูรณาการ และ (3) ประเมินผลก่อนและหลังการดำเนินตามรูปแบบ การวิจัยแบ่งเป็น 2 ระยะ คือ ระยะที่ 1 ศึกษาในผู้ป่วยเบาหวาน 372 คน และระยะที่ 2 ศึกษาในกลุ่มผู้พัฒนารูปแบบ เป็นผู้มีส่วนได้ส่วนเสียในพื้นที่ 192 คน และกลุ่มผู้ป่วยเบาหวานที่เข้าสู่กระบวนการพัฒนารูปแบบ 58 คน เก็บรวบรวมข้อมูลด้วยแบบสอบถามและแนวทางการสนทนากลุ่มที่พัฒนาขึ้น ระหว่างเดือน สิงหาคม - ธันวาคม 2568 วิเคราะห์ข้อมูลเชิงปริมาณด้วยสถิติเชิงพรรณนา และสถิติเชิงอนุมาน คือ สถิติ Multiple Linear Regression และ สถิติ Paired t-test ข้อมูลเชิงคุณภาพด้วยการวิเคราะห์เชิงเนื้อหา ผลการศึกษาพบว่า ปัจจัยที่มีผลต่อพฤติกรรมการดูแลตนเองผู้ป่วยเบาหวาน อย่างมีนัยสำคัญทางสถิติ ได้แก่ ความรู้ในการดูแลสุขภาพตนเอง (β = 0.07, 95%CI: 0.12 , 0.27) การกำกับตนเองทางด้านสุขภาพ (β = 0.04, 95%CI: 0.01 , 0.07) การดูแลตนเองทางด้านสุขภาพ (β = 0.90, 95%CI: 0.93 , 0.98) และผลการพัฒนารูปแบบการดูแลผู้ป่วยเบาหวาน โดยการประยุกต์แนวคิดรูปแบบการดูแลโรคเรื้อรังเชิงบูรณาการ จังหวัดพังงา ประกอบด้วย 7 กิจกรรม คือ (1) โปรแกรม ปรับเปลี่ยนพฤติกรรม สร้างเสริมสุขภาพ (2) พัฒนาระบบให้คำปรึกษา (3) จัดตั้ง DM Remission Clinic (4) จัดตั้งศูนย์ปฏิบัติการ NCDs ภาคประชาชน (5) จัดกระบวนการกำกับติดตามอาการอย่างต่อเนื่อง (6) กำหนดรูปแบบการดูแลโดยทีมสหสาขาวิชาชีพ ด้วยหลักเวชศาสตร์ครอบครัว และ (7) การจัดบริการส่งยาทางไปรษณีย์ ผลจากการใช้กิจกรรมตามรูปแบบที่พัฒนาขึ้น พบว่า ตัวอย่างสามารถหยุดการใช้ยาได้ 36 ราย (ร้อยละ 62.07) และมีค่าระดับน้ำตาลในเลือด (FBS) ลดลงอย่างมีนัยสำคัญทางสถิติ (Mean diff =32.18 mg/dl (S.D. = 15.39), 95%CI: 28.14 , 36.23) This research and development study had three objectives: (1) to examine factors influencing self‑care behaviors for blood glucose control among patients with diabetes, (2) to develop a diabetes care model by applying an integrated chronic care model, and (3) to evaluate outcomes before and after implementation of the model. The study was conducted in two phases: Phase 1 included 372 patients with diabetes, and Phase 2 included 192 local stakeholders who participated in model development and 58 patients with diabetes who were enrolled in the model implementation process. Data were collected using a structured questionnaire and a researcher‑developed focus group discussion guide between August - December 2025. Quantitative data were analyzed using descriptive statistics and inferential statistics, namely multiple linear regression and paired t‑test, while qualitative data were analyzed using content analysis. The results showed that factors significantly associated with self‑care behaviors among patients with diabetes were self‑care health knowledge (β = 0.07, 95% CI: 0.12–0.27), health self‑regulation (β = 0.04, 95% CI: 0.01–0.07), and health self‑care (β = 0.90, 95% CI: 0.93–0.98). The diabetes care model developed by applying the integrated chronic care concept in Phang Nga Province comprised seven key activities: (1) a health promotion and behavior change program, (2) development of a counseling system, (3) establishment of a DM Remission Clinic, (4) establishment of a community‑based NCDs operations center, (5) implementation of a continuous symptom monitoring and follow‑up process, (6) development of a multidisciplinary care model based on family medicine, and (7) provision of postal medication delivery services. Following implementation of the model, 36 participants (62.07%) were able to discontinue antidiabetic medication, and fasting blood sugar (FBS) levels decreased significantly (mean difference = 32.18 mg/dl, S.D. = 15.39, 95% CI: 28.14–36.23).